Influence of Risk Factors on Bone Density in Inflammatory Bowel Diseases - Dobrovoljski, Daniela; Jović, Duška; Knežević, Darija; Vlatković, Vlastimir (Scripta Medica, 2025)
Background/Aim: Young people and teenagers are often affected by chronic inflammatory bowel diseases, such as ulcerative colitis and Crohn’s disease. Prolonged and continuous inflammation, the release of inflammatory mediators with increased osteoclastic activity and reduced osteoblast activity, lead to accelerated bone mineral loss. Glucocorticoid (GC) utilisation in the pharmacotherapy of inflammatory bowel disease (IBD) and malabsorption are additional risk factors affecting bone mineral density (BMD). The main objective of this research was to assess the influence smoking, coffee, alcohol, physical activity and therapy on BMD in chronic inflammation the digestive system. Methods: A retrospective study included 30 respondents with IBD, average age 34.0 ± 6.73. Participants were divided according to the type of disease into the categories of Crohn disease - CD (n = 14) and ulcerative colitis - UC (n = 16). All patients had their BMD determined by osteodensitometry. Results: Osteopenia was present in 56.7 % of patients. A statistically significantly higher percentage of patients with UC had osteopenia (40 % vs 16.7 %, p < 0.05). Osteoporosis (OP) was not recorded in the study participants. Smoking and coffee consumption were the most common risk factors. Studying risk factors showed that treatment with GC therapy led to a statistically markedly reduced BMD in form of osteopenia in respondents with UC (40 % vs CD 16.7 %, p < 0.05). Conclusion: Presented study’s findings indicated that 50 % of the patients presented with reduced BMD in the form of osteopenia, which was more present in UC patients. In this study, only the use of GC had a statistically significant negative effect on BMD.